Pousadas em Caldas Novas(GO): a gestão e sua relação com o meio ambiente nos anos de 2015 a 2020 - Carvalho, Ronaldo do Nascimento (2023)
The present work brings about the management and its relationship with the environment in the years 2015 to 2020 of the inns in Caldas Novas, which is a municipality of Goiás that has a very high economic development driven by the growth of the large urban centers of the state. Naturally, this locality mixes local customs and, thought, mainly, in the form of organization of the tourist places, that is, appropriation of the urban spaces, mainly, population. It is possible to state that, through the modernization engendered in capitalist production, this territory has had a tourist dynamic that, due to this, managers have difficulties that cause the visible and disturbing impact in this region. The general objective is to analyze the management and its relationship with the environment in the years 2015 to 2020 of the inns in Caldas Novas. While the methodology is of a qualitative and quantitative approach, based on bibliographical, documentary and field research, using resources from books, articles, magazines, theses, dissertations, legislation, among other materials on Caldas Novas, found at the base of the Google Scholar and publications site related to the topic. As for the results, the surveys had their objectives achieved, showing that tourist activities and the management of inns have great responsibilitiesin the environmental impacts, based on the analyzes raised in these sectors. Finally, it is concluded that the constant significant increase of visitors, in Caldas Novas, causes the inns to be overcrowded, overloading their basic services, noting that this floating population starts to provide an increase in demand that results in the degradation local. However, it is summarized that tourist activities directly affect this municipality, harming the daily lives of residents of this city, considering that the management of these establishments is primarily responsible for negative experiences in this territory.